Screening of Hyperglycemic Patients Admitted in Intensive Care Unit - Kumar, Santosh; Arya, Awadhesh Kumar; Bihari, Ritwiz; Pokharia, Deepa; Kumar, Hemant; Tripathi, Kamlakar (Asian Journal of Medical Sciences, 2013)
Background & objectives: It is a prospective, randomized, controlled study involving adults admitted to medical Intensive care unit (ICU) who were receiving mechanical ventilation. Methods: On admission, patients were randomly assigned to receive intensive insulin therapy (maintenance of blood sugar at a level between 80 and 110 mg/dl) and were found to have hyperglycemic. We study the clinical profile of critically ill hyperglycemic patients and associated metabolic profiles of all such patients were analyzed in relation to final outcome. Results: The benefit of intensive insulin care was from 8.0 percent with conventional treatment to 4.6 percent (P<0.04, with adjustment for sequential analyses). Intensive insulin therapy to maintain blood glucose at or below 110mg per deciliter reduced the morbidity and motility among critically ill patients in the surgical intensive care unit. Hyperglycemia was present in 38% of patient admitted to the hospital, of whom 26% had a known history of diabetes, and 12% had no history of diabetes before admission. Interpretation & conclusions: New hyperglycemic patients had a longer length of hospital stay, a higher admission rate to an intensive care unit, and were less likely to be discharged to home, frequently requiring transfer to an intermediate care unit. DOI: http://dx.doi.org/10.3126/ajms.v5i1.8507 Asian Journal of Medical Science Vol.5(1) 2014 pp.63-69